KAJIAN PENURUNAN KADAR BESI (FE) PADA AIR SUMUR GALI MENGGUNAKAN METODE FILTRASI DENGAN VARIASI BESARAN BILANGAN IODINE PADA KARBON AKTIF - Istika - Sari; Muhammad Amin; Dwi Sat Agus Yuwana (Universitas Tidar, 2021)
Dermonganti hamlet, Ketitang village, Jumo Sub-distric, Temanggung distric is the area which most of the people use dug well water. The result from the three parameters that are tested. They are TDS, Ph, and iron rate (Fe) that is obtain from the result of iron rate (Fe) 2,56mg/l, 2,525mg/l 2,69 mg/L. The result is more than 1 mg/l means that exceeding the quality standards of maximum limit from the regulation of Minister of Health of the Indonesian Republic number 32 in the year 2017. So, dug well water processing is required through the filtration to reduce iron rate (Fe). The research used a tubular filtration contains a filter media that are sands, pumice, active carbon that have the magnitude of each iodine is 650mg/l, 800mg/l, 1000mg/l with each filter media thickness is 30cm. Parameter reviewed is iron rate (Fe). The processing is carried out with contact time 1 hour, 2 hours, 3hours for every variation. Data analysis used are regression analysis and Anova test. The result of filtration shows the highest removal value of iron rate (Fe) occurs to the 1 unit filtration with 1 hour contact time. The iron rate removal score (Fe) at 1 hour used filter 1 with the sand, pumice and active carbon as filter medias with the iodine number 1000mg/g with the percentage 59,17%. The greater its iodine number of activated carbon shows the increasing value of removal iron rate content.Key words: Iodine number, Filtration, Iron rate.